Medical students’ perception on the impact of mock Objective Structured Clinical Examination (OSCE) on final examination performance - Shanya Shanmugam; Rajeswari Kathirvel; Kayda Soh; Xinyi Li (The Asia Pacific Scholar)
Introduction: The Objective Structured Clinical Examination (OSCE) is a popular method for assessing medical students' clinical proficiency. Mock OSCEs are often incorporated into medical curricula to help students familiarise themselves with the examination format. While the impact of mock OSCEs on academic performance has been studied, their perceived utility remains less explored. This study aimed to assess the effectiveness of a mock OSCE in preparing medical students for their final examinations. Methods: A prospective study was conducted at a tertiary hospital in Singapore, involving medical students undergoing their Obstetrics and Gynaecology posting. The mock OSCE consisted of five stations and included immediate feedback from examiners. Students completed three questionnaires: pre-mock OSCE, post-mock OSCE and post final examinations, rating the utility of the session and their confidence levels. Results: Of the cohort of 147 students, 121 responded to the pre-mock OSCE survey, 132 responded to the post-mock OSCE survey, and 105 to the survey after their final examinations. The percentage of students who found the mock OSCE useful/very useful increased significantly from 97.5% before to 98.5% after the session, and significantly decreased to 96.2% after the examinations. Confidence levels rose significantly from a mean score of 2.34/5 pre-mock to 3.89/5 post-mock, to 4.67/5 post-exam. Qualitative feedback was positive, highlighting the benefit of familiarisation with examination mark schemes. Conclusion: The mock OSCE was well-received by students and perceived as a valuable tool in preparation for examinations. Despite the limited sample size, these findings support the implementation of mock OSCEs to enhance students' learning and exam preparedness.